Sensory evaluation and contamination test on mango fruit (Mangifera indica) puree - Amid, Azura; Jaswir, Irwandi; Othman, Muhd Ezza Faiez (IIUM Press, 2011)
Cancer is a disease which is known Ihroughoul the world. There arc many available commercial and alternalive treatments to Ireat cancer. Mango (Mungiferu indica L) is one the popular trOPical fru;ts found in Malaysia. A wide variety of mang0C5 can easily be fouod in this country, Mangoes are known for the;r vibrant flesh colour. juicy texture. sweet flavour. vitamins and minerals. Besides that. mango also contains anticancer and antiproliferation properties. Siamese mango was sekcted for oplimilation of purec sterilizatiOtl. Mango puree was Sterilized and stored for approximately five days. The sensory evaluation and contamination test was performed on sterilized lmd stored puree, Contamination test shows no growth for Staphylococcus aure"s and E. coli/colifonn. Puree 2 (8S°C. IS min sterilization lime and lC!u 970) and Puree 10 (8)<C, 8 min sterilization time. and IC~ 640) ha\'e satisfied most respondents, Variation of temperature and time for puree sterilization does affect the appearance. taste and tCJlture oftl>c puree.